Pengaruh Presepsi atas Media Pembelajaran dan Motivasi Belajar Terhadap Pemahaman Konsep Ilmu Pengetahuan Alam - Akmal, Dhea Harsyanti; Suedarti, Mamik; Erwinsyah (ALFARISI: Jurnal Pendidikan MIPA, 2026)
This study aims to determine the influence of perceptions of learning media and learning motivation on understanding science concepts. The research method used in this study is a survey method with correlation and regression analysis. The variables of perceptions of learning media and learning motivation were obtained by questionnaire, and data on understanding science concepts were obtained through the Natural Science Concept Understanding Ability Test on the digestive system for grade VIII students in the Odd Semester of the 2025/2026 Academic Year. The results of this study conclude that: 1) There is a significant influence of perceptions of learning media and learning motivation, together on understanding science concepts of students at MTs Negeri East Jakarta. This is evidenced by the obtained value of Sig = 0.008
Keywords: persepsi; media pembelajaran; motivasi; pemahaman konsep